EFFICIENCY OF BASE TREATMENT OF OBESITY FOR TEENAGERS: PROBLEM QUESTIONS - Senatorova, G.S.; Chaichenko, T.V.; Тельнова, Л.Г.; Lutaiy, T.V. (World of Medicine and Biology, 2012)
Efficiency of decline of mass of body teenagers have subzero enough, regardless of initial index of mass of body. It is set at a dynamic supervision, that 33,41 % teenagers and/or the members of their families are demonstrated by very subzero complaience in regard to the correction of ovenweight, namely categorically gave up the repeated inspection. By the most substantial factors which limit the observance of recommendations, phsyhosocial, namely insufficient support parents and yearlings, subzero availability of "healthy" foods of feed and amount of social establishments for engaging in physical education and sport.